A contrast between children and adolescents with excellent and poor control: the T1D exchange clinic registry experience. Issue 2 (19th August 2013) - Campbell, Meredith S; Schatz, Desmond A; Chen, Vincent; Wong, Jenise C; Steck, Andrea; Tamborlane, William V; Smith, Jennifer; Beck, Roy W; Cengiz, Eda; Laffel, Lori M; Miller, Kellee M; Haller, Michael J; et al.
ABSTRACT Objectives Optimizing glycemic control in pediatric type 1 diabetes (T1D) is essential to minimizing long‐term risk of complications. We used the T1D Exchange database from 58 US diabetes clinics to identify differences in diabetes management characteristics among children categorized as having excellent vs. poor glycemic control. Methods Among registry participants 6–17 yr old with diabetes duration ≥2 yr, those with excellent control [(A1c <7%)(53 mmol/mol) (N = 588)] were compared with those with poor control [(A1c ≥9% )(75 mmol/mol) (N = 2684)] using logistic regression. Results The excellent and poor control groups differed substantially in diabetes management (p < 0.001 for all) with more of the excellent control group using insulin pumps, performing blood glucose monitoring ≥5×/d, missing fewer boluses, bolusing before meals rather than at the time of or after a meal, using meal‐specific insulin:carbohydrate ratios, checking their blood glucose prior to giving meal time insulin, giving insulin for daytime snacks, giving more bolus insulin, and using a lower mean total daily insulin dose than those in poor control. After adjusting for demographic and socioeconomic factors, diabetes management characteristics were still strongly associated with good vs. poor control. Notably, frequency of severe hypoglycemia was similar between the groups while DKA was more common in the poorly controlled group. Conclusions Children with excellent glycemic control tend to exhibit markedly different diabetes self‐management techniques than those with poor control. This knowledge may further inform diabetes care providers and patients about specific characteristics and behaviors that can be augmented to potentially improve glycemic control.